An Application of Cuckoo Search Algorithm for Solving Optimal Chiller Loading Problem for Energy Conservation - M. H., Sulaiman; Muhammad Ikram, Mohd Rashid; Mohd Rusllim, Mohamed; Omar, Aliman; Hamdan, Daniyal (2014)
This paper presents a recent swarm intelligence technique viz. Cuckoo Search Algorithm (CSA) for solving the Optimal Chiller Loading (OCL) problem for energy conservation. Multi-chillers system has been widely used by commercial and industrial facilities to provide cooling energy. The main problem of multi-chillers system is that it conserved huge amount of energy. In this study, Partial Load Ratio (PLR) of the chiller is used as the variables to be optimized while the power consumption in kW is selected as the objective function to be minimized. On the other hand, CSA is a one of well-known swarm intelligence techniques that has been used to solve many optimization problems. In order to show the effectiveness of CSA in solving OCL problem, a case study with six-chiller system is considered. Results obtained are compared with other techniques available in literatures.